Protease-activated Receptor 2 Promotes Crohn's Disease-Associated Colonic Fibrosis through Fibroblast Activation - Wang, Zhaohui; Liu, Bin; Chu, Chenghao; Liu, Fubao (Current Molecular Medicine, 2025)
AimsTo clarify the roles of PAR-2 (protease-activated receptor 2) in Crohn's disease-associated colonic fibrosis.BackgroundG protein-coupled receptor, termed PAR-2, is triggered after serine proteases. Through activating genes encoding extracellular matrix proteins and proinflammatory cytokines, PAR-2 triggering promotes inflammatory / pro-fibrotic pathways. Although PAR-2 is highly expressed within the digestive system, its significance within colonic fibrosis (CF) has not yet been probed.ObjectiveTo assess the roles and mechanisms of PAR-2 in Crohn's disease-associated colonic fibrosis.MethodsPAR-2 expression was assessed variably in the colon of human and model mice. Immunofluorescence assay was used to analyze the phenotypic changes of fibroblasts after PAR-2 activation in the lamina propria. In in vitro assays, we explored the roles of PAR-2 in CCD-18Co fibroblasts treated with PAR-2 inhibitor ENMD-1068 and PAR-2 agonist SLIGRL-NH2.ResultsPAR-2 was highly expressed in the subepithelial layer surrounding colonic crypts of CD patients or murine fibrosis cohort. Colonic PAR-2 expression was consistent with collagen deposition. Decreasing PAR-2 in experimental colon fibrosis caused a decrease in the amount of colonic collagen and histological fibrosis, followed by a reduction in colonic fibroblast activation. PAR-2 activation enhanced CF by showing a profibrogenic phenotype and collagen synthesis within CCD-18Co fibroblasts.ConclusionOur results show that PAR-2 activation could upregulate extracellular matrix (ECM) proteomic levels, encourage CF, and cause a pro-fibrogenic phenotype within human colonic myofibroblasts.
Keywords: colonic fibrosis